Body shape trajectories and risk of breast cancer: results from the SUN ('Seguimiento Universidad De Navarra') Project. Issue 3 (10th February 2021) - Sanchez-Bayona, Rodrigo; Sayon-Orea, Carmen; Gardeazabal, Itziar; Llorca, Javier; Gea, Alfredo; Santisteban, Marta; Martín-Moreno, Jose M; Toledo, Estefania
Abstract: Objective: The aim of this study was to assess body shape trajectories in childhood and midlife in relation to subsequent risk of breast cancer (BC) in a Mediterranean cohort. Design: The 'Seguimiento Universidad de Navarra' (SUN) Project is a dynamic prospective cohort study of university graduates initiated in 1999. With a group-based modelling approach, we assessed body shape trajectories from age 5 to 40 years. Multivariable Cox regression models were used to estimate the hazard ratio (HR) for BC after the age of 40 years according to the body shape trajectory. Setting: City of Pamplona, in the North of Spain. Participants: 6498 women with a mean age of 40 years (sd 9). Results: We identified four distinct body shape trajectories ('childhood lean-midlife increase' (19·9 %), 'childhood medium-midlife stable' (53 %), 'childhood heavy-midlife stable' (21 %) and 'childhood heavy-midlife increase' (6·1 %)). Among 54 978 women-years of follow-up, we confirmed eighty-two incident cases of BC. Women in the 'childhood lean-midlife increase' group showed a higher risk of BC (HR = 1·84, 95 % CI 1·11, 3·04) compared with women in the 'childhood medium-midlife stable' category. This association was stronger for postmenopausal BC (HR = 2·42, 95 % CI 1·07, 5·48). Conclusions: Our results suggest a role for lifetime adiposity in breast carcinogenesis.